2005
DOI: 10.1111/j.0105-2896.2005.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunosenescence and macrophage functional plasticity: dysregulation of macrophage function by age‐associated microenvironmental changes

Abstract: The macrophage lineage displays extreme functional and phenotypic heterogeneity, which appears to be because, in large part, of the ability of macrophages to functionally adapt to changes in their tissue microenvironment. This functional plasticity of macrophages plays a critical role in their ability to respond to tissue damage and/or infection and to contribute to clearance of damaged tissue and invading microorganisms, to recruitment of the adaptive immune system, and to resolution of the wound and of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
144
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(158 citation statements)
references
References 188 publications
(247 reference statements)
6
144
0
1
Order By: Relevance
“…These data are also in agreement with studies suggesting that cytokines improve function of macrophages in the elderly (Hayakawa et al 1995;Stout and Suttles 2005). Our data showed that use of an IL-2/anti-CD40 Ab-based immunotherapy could be effective in elderly cancer-bearing hosts.…”
Section: Discussionsupporting
confidence: 92%
“…These data are also in agreement with studies suggesting that cytokines improve function of macrophages in the elderly (Hayakawa et al 1995;Stout and Suttles 2005). Our data showed that use of an IL-2/anti-CD40 Ab-based immunotherapy could be effective in elderly cancer-bearing hosts.…”
Section: Discussionsupporting
confidence: 92%
“…Tissue macrophages that are differentiated from the same precursor cells exhibit extensive variation in functions depending on their anatomic locations, and the maintenance of tissuespecific characteristics of macrophages is required for an organ to function normally (1,12,13). Residential intestinal macrophages display inflammatory anergy characterized by downregulated expression of innate response and growth factor receptors and reduced production of inflammatory cytokines but remain highly phagocytic (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…In aged people, the decline in phagocytic activity is associated with increased susceptibility to infectious agents that contributes to infectioninduced morbidity and mortality (Makinodan 1981). A reduction in number of phagocytes coupled with an intrinsic decline of their bactericidal activity has been observed in aged people (Strout and Suttles 2005). Also, there is a significant reduction in production of reactive oxygen intermediate (ROI) species in phagocytic cells (PMNs) in elderly.…”
Section: Introductionmentioning
confidence: 99%